1993
DOI: 10.1177/00220345930720110701
|View full text |Cite
|
Sign up to set email alerts
|

Co-activation of Sternocleidomastoid Muscles During Maximum Clenching

Abstract: In an attempt to determine the degree of co-activation present in selected cervical muscles during clenching, we instructed 12 male subjects to produce four brief maximum voluntary contraction (MVC) efforts (clenching) in a position of maximum intercuspation. Surface EMG activity was recorded bilaterally from the masseter and sternocleidomastoid (SCM) muscles. The contraction level for the SCM during clenching was reported as a percentage of the SCM's maximum activity achieved during maximum neck flexion again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
3
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 27 publications
5
65
3
4
Order By: Relevance
“…This is the first study to use kinesiologic EMG to evaluate the effect of occlusal support on masticatory, head and neck, trunk, and lower limb muscles simultaneously during complex functional tasks. Previous studies in dentate subjects reported alteration of muscular contraction pattern when the occlusal support was modified by introducing an experimental interference (1,(11)(12)(13)(14)(15)(16). However, these studies used static positions; only Sasaki et al (12) evaluated isometric and isokinetic exercises of the lower limbs and did not find any association between dental clenching and isokinetic exercises.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study to use kinesiologic EMG to evaluate the effect of occlusal support on masticatory, head and neck, trunk, and lower limb muscles simultaneously during complex functional tasks. Previous studies in dentate subjects reported alteration of muscular contraction pattern when the occlusal support was modified by introducing an experimental interference (1,(11)(12)(13)(14)(15)(16). However, these studies used static positions; only Sasaki et al (12) evaluated isometric and isokinetic exercises of the lower limbs and did not find any association between dental clenching and isokinetic exercises.…”
Section: Discussionmentioning
confidence: 99%
“…In Dentistry most studies using EMG have analyzed the activity of masticatory and head and neck postural muscles in static conditions, such as rest, maximum mouth opening, and dental clenching. Coordination of masticatory, head and trunk postural muscles, and muscles of lower extremities were reported during voluntary maximum clenching in dentate subjects (11)(12)(13). Asymmetric contractions of masticatory (14), neck (15), and leg (16) muscles were observed during dental clenching against an occlusal interference.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between the vestibular nuclei and trigeminal system, which is then employed by the visual system and used for postural control and maintenance, strengthens the interaction between the stomatognathic system and postural control [23,[32][33][34][35][36]. Through this mechanism, interactions occur not only at the position of the mandible and cranial bone, hyoid bone, cervical spine, and subhyoid structures, but also at the position of the shoulders and dorsal and lumbar spine in TMD patients [21,37,38].…”
Section: Mechanism Of Body Postural Controlmentioning
confidence: 99%
“…Sternocleidomastoid muscle is directly stimulated by the cervical segments of spinal accessory nerve and cervical C2, C3 and C4. This muscle has a great role in important pathologies like headache and vertigo (Clark et al 1993). As seen in certain studies, when the neck is stabilized, activation of neck flexor muscle is higher in the subjects having cervical pain when compared to healthy subjects (Jull 2000;Sterling et al 2001).…”
Section: Scm and Abdominal Muscles Activity During Curl-up Exercisementioning
confidence: 99%